microRNAs and Their Roles in Plant Development - Dong, Qingkun; Hu, Binbin; Zhang, Cui (Frontiers in Plant Science, 2022)
Small RNAs are short non-coding RNAs with a length ranging between 20 and 24 nucleotides. Of these, microRNAs (miRNAs) play a distinct role in plant development. miRNAs control target gene expression at the post-transcriptional level, either through direct cleavage or inhibition of translation. miRNAs participate in nearly all the developmental processes in plants, such as juvenile-to-adult transition, shoot apical meristem development, leaf morphogenesis, floral organ formation, and flowering time determination. This review summarizes the research progress in miRNA-mediated gene regulation and its role in plant development, to provide the basis for further in-depth exploration regarding the function of miRNAs and the elucidation of the molecular mechanism underlying the interaction of miRNAs and other pathways.